Maqāṣid Al-Sharī'ah In Interfaith Zakat Distribution: An Analysis of Islamic Civilization's Response to Religious Plurality in Banyuwangi - Mustain Hakim; Akhmad Zaeni; Moh. Mahfud Ihsan Azzamami; Moh Ferdi Hasan (TSAQAFAH, 2026)
This study examines the theological and philosophical foundations of interfaith zakat distribution in Yosomulyo Village, Banyuwangi Regency, through the lens of maqāṣid al-sharī'ah and historical Islamic jurisprudence. While classical fiqh predominantly restricts zakat to eight categories (asnaf) of Muslim recipients, the practice in Yosomulyo presents a unique case where Islamic philanthropic instruments (zakat, infaq, and sadaqah) are distributed across religious boundaries. This research employs a qualitative case study methodology with Islamic philosophical-historical analysis, examining primary texts from classical madhahib, particularly the Hanafi school's position on zakat distribution to non-Muslims, alongside contemporary maqāṣid interpretations by Yusuf al-Qaradawi. Data were collected through semi-structured interviews with 20 Islamic scholars and community leaders, participatory observation of 5 ZIS distribution events, and document analysis. The findings reveal a sophisticated theological framework operating through a three-tiered legal hierarchy: (1) textual foundations (naṣṣ) differentiating between restricted zakat funds (muqayyad) exclusively for Muslim asnaf and unrestricted sadaqah (mutlaqah) permissible for interfaith distribution; (2) jurisprudential mechanisms (fiqh) grounded in the Ḥanafī school's allowance for zakat al-fiṭr to non-Muslim poor based on the effective cause ('illah) of meeting basic subsistence needs (kifyah) rather than strengthening religious solidarity (ta'āwun dīnī); and (3) higher objectives (maqāṣid) where interfaith sadaqah fulfills the ḍarūriyyāt (necessity) level of preserving community cohesion (ḥifẓ al-mujtama') and preventing social harm (dar' al-mafāsid), elevated from mere permissibility (ibāḥah) to contextual ethical obligation (wājib 'urfi) in pluralistic settings. This distinction is implemented through strict institutional mechanisms: dual-audit accounting systems (PSAK 109/409), separate ledgers for each fund type verified by shariah compliance officers, and unified distribution ceremonies that symbolically integrate fund segregation with civilizational solidarity. The implications extend beyond mere philanthropy, constructing what we term "civilizational solidarity" (al-takāful al-ḥaḍārī) that embodies Islamic civilization's historical capacity to maintain religious identity while fostering pluralistic harmony—a replicable model whose critical feature combines juridical rigor in fund separation with cultural synthesis in social practice.